Avant-propos : Retour sur le débat relatif aux territoires de chasse familiaux algonquiens - Morantz, Toby (Anthropologica, 2018)
Thirty-two years ago Anthropologica dedicated a double issue to the controversies and arguments swirling around northern Algonquian land tenure, specifically the nature of the family hunting territories first identified and named in 1915 by Frank Speck, whose framework followed the lines of Western ideas about property. By 1970, the dominant voices on this issue were those of Eleanor Leacock and Julian Steward, both of whom refuted Speck's claim that this land tenure system was Aboriginal. They maintained that it emerged from the European fur trade. So vigorous was this opposition that it came to be seen as a debate. Anthropology students in the 1970s discovered that the family hunting territories, specifically among the east Cree of James Bay, the Eeyou Istchee, did not mirror the writings in the literature. Looking back at the 1986 publication, this foreword reviews the history of the debate and draws from the articles the major claims of each writer on Cree practices and other subarctic peoples. Some of the topics reviewed are the nature of territoriality, the flexibility of the Cree system, the expectations of the hunting bosses, the overlap of the more traditional and government systems, and resource management and historical documentation of the early existence of the family hunting territories. As a result of Leacock having framed her denial of an early development of family hunting territories within the context of primitive communism, this theme, too, is reviewed.